2000
DOI: 10.1007/s11664-000-0244-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and control of voids and void-hillocks during molecular beam epitaxial growth of HgCdTe

Abstract: Void defects were demonstrated to form away from the substrate-epifilm interface during the molecular beam epitaxial growth of mercury cadmium telluride on cadmium zinc telluride substrates. These were smaller in size compared to voids which nucleated at the substrate-epifilm interface, which were also observed. Once nucleated, voids usually replicated all the way to the surface even if the flux ratios were modified to prevent additional nucleation of voids. Occasionally, void defects which close before reachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 6 publications
1
13
2
Order By: Relevance
“…As the Hg deficient environment continues, the void expands; altering the Hg constituent may prevent the voids from growing too large, but the crystallinity cannot be recovered, and the void remains throughout the growth. 6,7,9 Chandra et al 10 observed voids that were entirely contained below the surface; this was not observed in this study. Energy dispersive x-ray analysis (EDXA) has been performed on the cleaved sample ( Fig.…”
Section: Physical Characteristics Of Void Defectscontrasting
confidence: 48%
See 1 more Smart Citation
“…As the Hg deficient environment continues, the void expands; altering the Hg constituent may prevent the voids from growing too large, but the crystallinity cannot be recovered, and the void remains throughout the growth. 6,7,9 Chandra et al 10 observed voids that were entirely contained below the surface; this was not observed in this study. Energy dispersive x-ray analysis (EDXA) has been performed on the cleaved sample ( Fig.…”
Section: Physical Characteristics Of Void Defectscontrasting
confidence: 48%
“…[2][3][4][5] Opportunities for performance improvement exist by reducing growth defects, in particular macrodefects such as voids, which can reduce FPA operability. Previous papers [6][7][8][9][10] have examined in depth the physical nature of voids and direct pixel-to-pixel correlation for single-color, mid-wavelength infrared (MWIR), MBE-grown HgCdTe/CdTe/Si FPAs. 11 However, direct correlation of defects to two-color device performance has not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…Large void defects with sizes from several micrometers to tens of micrometers are the most common defect in MBE-grown HgCdTe. They arise as a consequence of Hg-deficient growth conditions, and are called either voids, 1,9,[40][41][42][43][44][45][46][47][48][49][50] crater defects, 6,10,22,23 V-shape 37 The directions of the crosshatched lines as well as the characteristic angles are labeled. The arrows show that the crosshatch lines are sometimes terminated by etch pits, namely dislocations in the crystal.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Although IV-VI semiconductors such as Pb 1-x Sn x Se show a high capability in comparison with II-VI and III-V materials, such as Hg 1-x Cd x Te and InSb, 6,7 not much effort has been devoted to exploring the full potential of IV-VI materials; for example, in the prevailing II-VI material, Hg 1-x Cd x Te, various growth defects have been identified such as dislocations, stacking faults and twins, voids and hillocks, as well as precipitates. [8][9][10] A similar study of the growth defects related to IV-VI materials, however, has not yet been implemented. This article will present an investigation of growth defects in PbSe epilayers grown by molecular beam epitaxy (MBE).…”
Section: Introductionmentioning
confidence: 99%